PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PT X DI JAKARTA - Nabila Rezqi Prameswari; Hendra Permadi; Darmeinis, Darmeinis (Bajang Institute, 2025)
This study aims to analyze the effect of incentives on employee performance at PT X in Jakarta. The research method used in this study is a descriptive method with a quantitative approach, employing data collection techniques through questionnaires distributed to employees of PT X. The population in this study consisted of 55 employees of PT X in Jakarta at the time the research was conducted. The data used in this research include both primary and secondary data, with simple regression analysis applied to determine the effect of incentives on employee performance. The results of this study show that incentives have a significant influence on employee performance. Based on simple linear regression analysis, it was found that incentives have a positive and significant effect on employee performance, with a constant value of 20.391 and a regression coefficient of 0.858. The significance value of 0.000 and t-count of 6.366 further confirm that the relation